SPECIFIC GYRB SEQUENCE OF MYCOBACTERIUM TUBERCULOSIS CLINICAL ISOLATED FROM SPUTUM OF PULMONARY TUBERCULOSIS PATIENTS IN INDONESIA - Mertaniasih, Ni Made; Wiqoyah, Nurul; Kusumaningrum, Deby; Soedarsono, S.; Perwitasari, Agnes Dwi Sis; Artama, Wayan Tunas (BALI MEDICAL JOURNAL; Vol 3 No 3 (2014), 2014)
Background: Indonesia have many different geographic areas which could be various on the  variant strains of Mycobacterium tuberculosis . The gyrB gene codes GyrB protein as sub unit  compound of Gyrase enzyme that functioning in multiplication of bacteria. Detection of gyrB gene  could be a marker of active multiplication of viable bacteria in the specimen from patients; and  some of the DNA sequence regions were conserved and specific in the strain of Mycobacterium tuberculosis that would be a marker for identification. This research aims to analyze the sequence  of gyrB gene of Mycobacterium tuberculosis clinical isolates from sputum of pulmonary TB patients  in Indonesia, and determine the specific region. Method : Mycobacterium tuberculosis clinical  isolates have been collected from sputum of the patients with pulmonary TB that live in some  area in Indonesia. Isolation and identification of  Mycobacterium tuberculosis clinical isolates  using standard culture method; sequence analysis using PCR-direct sequencing of the part  bases region of gyrB. Results : this study revealed that nucleotide sequence on a fragment 764 bases  of gyrB gene Mycobacterium tuberculosis strains among clinical isolates almost identically to a  wild type strain Mycobacterium tuberculosis H37Rv and subspecies member of Mycobacterium tuberculosis complex (MTBC), with a little difference of SNPs; there are many difference  nucleotide sequence with MOTT and Gram positive or negative bacteria, except Corynebacterium diphtheria identically with MTBC. Conclusion : the gyrB sequence in Mycobacterium tuberculosis strains among these clinical isolates from sputum of pulmonary TB patients in Indonesia have  the conserved specific DNA region that almost identically with wild type strain H37Rv and MTBC.
Keywords: sequence; gyrB gene; Mycobacterium; tuberculosis; sputum.